99mTc-labeled single-domain antibody EG2 in targeting epidermal growth factor receptor. Issue 5 (May 2015) - Li, Chongjiao; Wen, Bing; Wang, Lifei; Feng, Hongyan; Xia, Xiaotian; Ding, Zhiling; Gao, Bin; Zhang, Yongxue; Lan, Xiaoli
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to explore the targeting ability and metabolic characteristics of the technetium-99m-labeled single-domain antibody (99mTc-sdAb) EG2 targeting epidermal growth factor receptor (EGFR) through an in-vitro and in-vivo study. Materials and methods The sdAb EG2 was radiolabeled with 99mTc using a tricarbonyl kit. The EGFR expression level of A431 and OCM-1 cells was confirmed using immunofluorescence staining. Cell binding, blocking, uptake, and efflux studies were performed to investigate the binding specificity of 99mTc-sdAb EG2 in vitro. Single-photon emission computed tomography imaging and biodistribution studies were used to explore the targeting abilities and metabolic characteristics of 99mTc-sdAb EG2 in vivo. Results 99mTc-sdAb EG2 was successfully prepared with labeling yields of 60–71% and specific activity of 1.83±0.29 GBq/mg (n=3). Immunofluorescence staining revealed high and low EGFR expression on the surface of A431 and OCM-1 cells, respectively. The binding affinity of 99mTc-sdAb EG2 to A431 cells was 43.53±1.89 nmol/l. 99mTc-sdAb EG2 uptake in A431 cells in vitro could be blocked by ∼19, 40, and 66% in the presence of excess unlabeled sdAb EG2 at 100, 500, and 1000 nmol/l, respectively. Single-photon emission computed imaging indicated that A431 tumor images could be clearly displayed at early scan time points after 99mTc-sdAb EG2 injection, even as early as 1 h. Biodistribution study showed that the A431 tumor uptake of 99mTc-sdAb EG2 was blocked by about 51% at 3 h after coinjecting excess of sdAb EG2. However, there were almost no OCM-1 tumor images at the corresponding scan time points and the OCM-1 tumor uptake was only 0.40±0.13% injected dose per gram of tissue (n=5) at 3 h. Conclusion This study demonstrated that sdAb EG2 can effectively target EGFR in vitro and in vivo in tumors, suggesting that it could be used as a molecular probe for EGFR detection.